A model for implementing guidelines for person-centered care in a nursing home setting. (19th August 2014) - Vikström, Sofia; Sandman, Per-Olof; Stenwall, Ewa; Boström, Anne-Marie; Saarnio, Lotta; Kindblom, Kristina; Edvardsson, David; Borell, Lena
ABSTRACT: Background: Systematic evaluations of knowledge translation interventions in nursing homes to improve practice are scarce. There is also a lack of studies focusing on creating sustainable evidence-based practice in the setting of residential dementia care. Methods: The aim of this paper is to describe a model for implementing national evidence-based guidelines for care of persons with dementia in nursing homes. The secondary aim is to outline the nursing home staff experiences during the first year of the implementation process. The intervention had a participatory action research approach. This included educational activities such as: (i) thematic seminars introducing national guidelines for dementia care, (ii) regular unit-based seminars; and (iii) later dissemination of information in reflective seminars and several days of poster-exhibitions. Areas of practice development were selected on each of the 24 units, based on unit-specific needs, and a quality improvement strategy was applied and evaluated. Each unit met ten times during a period of eight months. Data for this study were extracted from the reflective seminars and poster presentations, analyzed using a qualitative content analysis. Results: Findings showed that implementation of guidelines were perceived by staff as beneficial for both staff and the residents. However, barriers to identification of relevant sources of evidence and barriers to sustainable implementation were experienced. Conclusions: One of our assumptions was that dementia nursing homes can benefit from becoming knowledge driven, with care practices founded in evidence-based sources. Our findings show that to be partly true, even though most staff units found their efforts to pursue and utilize knowledge adversely impacted by time-logistics and practical workload challenges.